Dynamic Simulation of Adiabatic Catalytic Fixed-Bed Tubular Reactors: A Simple Approximate Modeling Approach - Wiwut Tanthapanichakoon; Shinichi Koda; Burin Khemthong (ASEAN Journal of Chemical Engineering, 2014)
Fixed-bed tubular reactors are used widely in chemical process industries, for example, selective hydrogenation of acetylene to ethylene in a naphtha cracking plant. A dynamic model is required when the effect of large fluctuations with time in influent stream (temperature, pressure, flow rate, and/or composition) on the reactor performance is to be investigated or automatically controlled. To predict approximate dynamic behavior of adiabatic selective acetylene hydrogenation reactors, we proposed a simple 1-dimensional model based on residence time distribution (RTD) effect to represent the cases of plug flow without/with axial dispersion. By modeling the nonideal flow regimes as a number of CSTRs (completely stirred tank reactors) in series to give not only equivalent RTD effect but also theoretically the same dynamic behavior in the case of isothermal first-order reactions, the obtained simple dynamic model consists of a set of nonlinear ODEs (ordinary differential equations), which can simultaneously be integrated using Excel VBA (Visual BASIC Applications) and 4th-order Runge-Kutta algorithm. The effects of reactor inlet temperature, axial dispersion, and flow rate deviation on the dynamic behavior of the system were investigated. In addition, comparison of the simulated effects of flow rate deviation was made between two industrial-size reactors.Keywords: Dynamic simulation, 1-D model, Adiabatic reactor, Acetylene hydrogenation, Fixed-bed reactor, Axial dispersion effect